Are Messages about Fruit and Vegetable Consumption Getting Through? - Pettigrew, Simone; Pescud, M.; Donovan, Robert (-, 2009)
Low and medium SES children’s knowledge of the Australian Government’s recommendations for minimum daily intakes of fruit and vegetables and their reported actual intakes were investigated. In total, 524 children and 123 parents from four Australian schools responded to questionnaires on the topic of children’s fruit and vegetable preferences and intakes. Around half the children could accurately state the publicised fruit and vegetable daily intake guidelines (two servings of fruit and five servings of vegetables) and low SES children were more likely to be able to do so. Contrary to expectation, around a quarter of the children nominated fruit or vegetables as their favourite foods. Recommendations for social marketing programs designed to increase fruit and vegetable consumption among children are provided.